Impact of mothers’ and fathers’ math self-concept of ability, child-specific beliefs and behaviors on girls’ and boys’ math self-concept of ability - Paulina Feige; Rainer Watermann; Sandra Simpkins; Jacquelynne Sue Eccles; Elisa Oppermann (PLoS ONE, 2025)
The present study investigated the longitudinal direct and indirect relations between mothers’ and fathers’ math ability self-concept, their child-specific math performance expectations and encouragement of math and science-related activities at home, and girls’ and boys’ math ability self-concept. Structural equation models were performed with longitudinal data from three waves of the Childhood and Beyond Study (CAB). The final sample consisted of 517 children and their mothers and fathers. The majority of children attended 2nd (26.1%), 3rd (25.5%) or 5th (40.4%) grade at first measurement point. Our results suggest that mothers and fathers with higher math ability self-concepts had higher expectations of their sons and encouraged their sons more, but not their daughters. Fathers’ math ability self-concept was indirectly related to the self-concept of their sons and this association was mediated by performance expectations. Furthermore, both boys and girls profited from their fathers’ expectations and girls benefitted from their fathers’ encouragement of math and science-related activities at home. In contrast, we found no effects from mothers’ beliefs and behaviors on child’s math ability self-concept. The findings underscore the relevance of fathers’ educational participation in the development of the math self-concept of ability of their children.